2020
DOI: 10.21203/rs.3.rs-38910/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiologic characteristics of orthopedic surgical site infections and under-reporting estimation of registries using capture-recapture analysis

Abstract: BackgroundSurgical Site Infections (SSIs) are among the leading causes of the postoperative complications. This study aimed at investigating the epidemiologic characteristics of orthopedic SSIs and estimating the under-reporting of registries using the capture-recapture method.MethodsThis study, which was a registry-based, cross-sectional one, was conducted in six educational hospitals in Tehran during a one-year period, from March, 2017 to March, 2018. The data were collected from two hospital registries (Nat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It was reported that the incidence rate of surgical site infection, accounting globally for about 10%–20% of all nosocomial infections, represents the most common type of health care‐associated infection. The most frequently reported microorganisms are Gram‐negative E. coli and Gram‐positive S. aureus causing implantation site infection in surgical procedures 84 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the incidence rate of surgical site infection, accounting globally for about 10%–20% of all nosocomial infections, represents the most common type of health care‐associated infection. The most frequently reported microorganisms are Gram‐negative E. coli and Gram‐positive S. aureus causing implantation site infection in surgical procedures 84 …”
Section: Discussionmentioning
confidence: 99%
“…The most frequently reported microorganisms are Gram-negative E. coli and Gram-positive S. aureus causing implantation site infection in surgical procedures. 84 Typically, the additions of ions, such as Ag and Cu, to metallic alloys inhibit bacterial growth. 61 Up until now, research has confirmed an antibacterial activity of Ag-rich or Cu-rich Zn-alloys in vitro.…”
Section: Antibacterial Activity-beneficial Property In Implant Materialsmentioning
confidence: 99%